High prevalence of ESBL-positive bacteria in an obstetrics emergency hospital and neonatal care unit—Haiti, 2016. (30th August 2018) - Chaintarli, Katerina; Lenglet, Annick; Beauzile, Bregeneve Dabord; Senat-Delva, Rodnie; Mabou, Marie-Marcelle; Martino, Chiara; Berthet, Marine; Wong, Sidney; Hopman, Joost
Abstract: A point-prevalence survey of mothers and neonates admitted to an obstetrics emergency hospital in Port-au-Prince, Haiti, revealed that 13 of 127 gram-negative bacteria isolates (10%) from rectal swabs were ESBL-positive in women and 30 of 59 gram-negative bacteria isolates (51%) from rectal swabs were ESBL-positive in neonates. Length of hospital stay and antibiotic consumption were risk factors for ESBL colonization.